Methods of forming threshold value of risk’sin financial sector index - D. A. Bezukhov; M. A. Khalikov (Путеводитель предпринимателя)
Problems of choosing justified value of equity ratio characterizing by admissible risk of financial sector in concerned enterprise are studied. As methods of modeling this value the approximation of relation in pair «cost of loan capital - equity ratio»by third degree Lagrange polynomial in which coefficients are calculated basis on values of this pair in a certain period of time is suggested.